2022
DOI: 10.11591/ijeecs.v28.i1.pp460-469
|View full text |Cite
|
Sign up to set email alerts
|

Game innovation: a case study using the Kizzugemu visual novel game with Tyranobuilder software in elementary school

Abstract: This research aims to find out the innovation of the Kizzugemu visual novel game with TyranoBuilder software in elementary school Javanese language learning. The lack of game media innovation in elementary school Javanese language learning is the background of this research. The research method is descriptive and qualitative, with data mining techniques; observation, indepth interviews, and documentation that present the results of descriptions of the innovation, features, application, and impact of using the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 14 publications
(15 reference statements)
0
7
0
1
Order By: Relevance
“…The subject of this research is the perpetrator who uses rajah pelaris. The method used by the author in this research is a qualitative research method with a phenomenological approach (Al-Ayyubi, 2016;Nuraedah & Mutawakkil, 2020;Hamidulloh et al, 2022). The data collection techniques used in this research are observation, interviews and structured documentation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The subject of this research is the perpetrator who uses rajah pelaris. The method used by the author in this research is a qualitative research method with a phenomenological approach (Al-Ayyubi, 2016;Nuraedah & Mutawakkil, 2020;Hamidulloh et al, 2022). The data collection techniques used in this research are observation, interviews and structured documentation.…”
Section: Methodsmentioning
confidence: 99%
“…The principle of hard work is a real step that can lead to success, but must go through a process full of obstacles. People who dare to go through great risks will get great sustenance opportunities (Hasyim, 2018;Hamidulloh et al, 2020;Wadewitz, 2023). In this context, the Qur'an talks a lot about life issues.…”
Section: Introductionmentioning
confidence: 99%
“…Pasalnya, hasil belajar adalah salah satu aspek yang menentukan keberhasilan proses pembelajaran (Juniati & Widiana, 2017). Realitasnya, guru MI di Indonesia belum menerapkan model DOI: 10.30762/sittah.v3i2.522 Amanda Fathin Furroyda, Hamidulloh Ibda, Andrian Ganjar Wijanarko, Pengaruh Model Pembelajaran Contextual Teaching and Learning berbasis TPACK terhadap Hasil Belajar PPKn di Madrasah Ibtidaiyah Swasta [147] pembelajaran kontekstual dan berbasis teknologi, game, aplikasi, dan peranti digital lainnya (Ibda et al, 2022), serta technological pedagogical and content knowledge (TPACK) secara umum di dalam pembelajaran (Ginting et al, 2022), termasuk guruguru MI di wilayah Kabupaten Temanggung.…”
Section: Pendahuluanunclassified
“…Other research has found that the demands of the digital era have not been mastered by teachers. One of the competencies of teachers in the digital era must master information literacy, process and search for digital-based data for learning purposes [9]. Another research reveals that teachers needed to adjust to the Industrial Revolution 4.0 age.…”
Section: Introductionmentioning
confidence: 99%
“…Other research stated that the ability of elementary school teachers in Indonesia to master information and communication technology (ICT) for learning [9], such as Moodle, comic media, mobile learning media, and other e-learning applications still need improvement [14], [15] Beside of master pedagogical, personality, social and professional competencies, in current development is required by a teacher to master competencies to make use of information, information technology, and mastery of new technologies in facilitating learning activities [16]. Efforts to improve quality and professional competence must be carried out by teachers in addition to pedagogical, personality, and social aspects [17].…”
Section: Introductionmentioning
confidence: 99%